Laminated microfluidic system for small sample protein analysis - Saedinia, Sara (AIP Publishing LLC, 2014)
We describe a technology based on lamination that allows for the production of highly integrated 3D devices suitable for performing a wide variety of microfluidic assays. This approach uses a suite of microfluidic coupons (“microfloupons”) that are intended to be stacked as needed to produce an assay of interest. Microfloupons may be manufactured in paper, plastic, gels, or other materials, in advance, by different manufacturers, then assembled by the assay designer as needed. To demonstrate this approach, we designed, assembled, and characterized a microfloupon device that performs sodium-dodecyl-sulfate polyacrylamide gel electrophoresis on a small sample of protein. This device allowed for the manipulation and transport of small amounts of protein sample, tight injection into a thin polyacrylamide gel, electrophoretic separation of the proteins into bands, and subsequent removal of the gel from the device for imaging and further analysis. The microfloupons are rugged enough to handle and can be easily aligned and laminated, allowing for a variety of different assays to be designed and configured by selecting appropriate microfloupons. This approach provides a convenient way to perform assays that have multiple steps, relieving the need to design highly sophisticated devices that incorporate all functions in a single unit, while still achieving the benefits of small sample size, automation, and high speed operation.